1991
DOI: 10.1111/j.1365-2885.1991.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of parenterally administered danofloxacin in cattle

Abstract: Danofloxacin is a new fluoroquinolone antibacterial, developed specifically for veterinary use. Its in vitro activity and pharmacokinetic properties have been investigated to assess its potential for use in the therapy of respiratory disease in cattle. The minimum inhibitory concentration of danofloxacin against 90% (MIC90) of contemporary European and North American field isolates of Pasteurella haemolytica, Pasteurella multocida and Haemophilus somnus, the most important bacterial respiratory pathogens of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 11 publications
3
43
1
Order By: Relevance
“…The pharmacokinetics of danofloxacin has been investigated in ruminant species including cattle (7,8,10), sheep (12), and goats (19). Following administration of danofloxacin, there is rapid distribution to the lungs (12) and high tissue concentrations are achieved in pneumonic lung, including areas of consolidation (1, 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacokinetics of danofloxacin has been investigated in ruminant species including cattle (7,8,10), sheep (12), and goats (19). Following administration of danofloxacin, there is rapid distribution to the lungs (12) and high tissue concentrations are achieved in pneumonic lung, including areas of consolidation (1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations for signs of bovine respiratory disease and measurement of rectal temperature were carried out immediately prior to inoculation, immediately prior to treatment administration at time zero, and at 4,8,12,24,36, and 48 h thereafter. The respiratory rate, rectal temperature, character of respiration, and general demeanor were assessed for each calf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It achieves high concentrations in several tissues, including the lung (11,22,23,33). Moreover, studies in our laboratory have demonstrated that the volume of distribution exceeds 3 liters/kg in four ruminant species after intravenous (i.v.)…”
mentioning
confidence: 99%
“…In fact they have been used successfully to treat infection caused by Gram positive and Gram negative bacteria. These compounds act by inhibiting the bacterial DNAgyrase (Gilles et al, 1991). Chemical structure of fluroquinolones when changed, an increase in the spectrum of activity and potency of the drugs is seen (Spoo et al, 1995).Enrofloxacin is one of the antibacterial agent which is widely used in veterinary medicine (Nouws et al, 1988).…”
Section: Introductionmentioning
confidence: 99%